Associations of socio-demographic, environmental and parental factors, and nutritional status with fast food consumption among children aged 7-11 years old in Selangor - Hui, Chong Shao; Mohd Shariff, Zalilah (Malaysian Journal of Nutrition, 2024)
Introduction: This cross-sectional study examined fast food consumption and its associated factors among primary school children in Selangor. Methods: A total of 221 children aged 7-11 years from six randomly selected primary schools in Petaling Perdana, Gombak, and Hulu Langat participated in this study. Parents completed a self-administered questionnaire on socio-demographic characteristics, exposure to fast food advertising, home food availability, parental stress, attitude towards fast food, intake of fast food, and two-day dietary record of children. Height and weight of children were obtained from their school SEGAK records. Results: Mean age of children was 9±1 years. Mean days per week of fast food consumption among children was 3.2±1.6 days, with 45.7% consuming fast food for?>3 days/ week. Factors associated with frequent fast food consumption were children whose fathers had non-tertiary education levels (aOR 2.53, 95% CI 1.18–5.40), children with higher total screen viewing time (aOR 1.21, 95% CI 1.00–1.46), lower home food availability score (aOR 0.87, 95% CI 0.76–0.98), overweight and obese (aOR 2.38, 95% CI 1.23–4.60), requiring dietary improvements (aOR 4.03, 95% CI 1.36–11.98), and with poor diet quality (aOR 5.08, 95% CI 1.57–16.44). Conclusion: More than one third of the children consumed fast food for?>3 days/week. Screen viewing time and home food availability should be considered when promoting healthy diets among children. Future research should consider other potential factors associated with children’s consumption of fast food.